Healthcare utilisation in children with SMA type 1 treated with nusinersen: a single centre retrospective review. Issue 1 (5th December 2019) - Ali, Imran; Gilchrist, Francis J; Carroll, William D; Alexander, John; Clayton, Sadie; Kulshrestha, Richa; Willis, Tracey; Samuels, Martin
Abstract : Background: Nusinersen has been used to treat spinal muscular atrophy type 1 (SMA1) in the UK since 2017. While initial trials showed neuromuscular benefit from treating SMA1, there is little information on the respiratory effects of nusinersen. We aimed to look at the respiratory care, hospital utilisation and associated costs in newly treated SMA1. Methods: We reviewed the medical records of all children within the West Midlands with SMA1 treated with nusinersen at Royal Stoke University Hospital. Baseline demographics and hospital admission data were collected including: the reason for admission, total hospital days, days of critical care, days intubated, discharge diagnosis, doses of nusinersen and treatment complications. Results: 11 children (six girls) received nusinersen between May 2017 and April 2019. Their median (range) age was 29 (7–97) months. The median (range) number of nusinersen doses per child was 6 (4–8). All children were receiving long-term ventilatory support; this was mask ventilation in nine and tracheostomy ventilation in two. The total number of hospital days since diagnosis was 1101 with a median (range) of 118 (7–235) days per child. This included general paediatric ward days 0 (0–63), High Dependency Unit 79 (7–173) days and Paediatric Intensive Care Unit 13 (0–109) days per child. This equated to a median (range) of 20 (2–72) % of their life in hospital. The estimated cost of this care was £2.2M. Conclusion: Patients with SMA1 treated with nusinersen initially spend a considerable proportion of their early life in hospital. Parents should be counselled accordingly. These data suggest that for every 10 children started on nusinersen an extra HDU bed is required. This has a significant cost implication.